Reforming the U.S Stockholding and Voting Systems - Al Sharqawi, Hadeel (Universidad Pompeu Fabra, 2020)
The introduction of the indirect holding system ("IHS") in the US caused serious inefficiencies to shareholder voting. The stockholding system could no longer trace share ownership to any particular shareholder. This triggered a series of legal changes,among them the creation of a proxy voting system where voting rights are passed from the central security depository ("CSD"),to brokers/ banks,and other types of intermediaries in the IHS all the way to shareholders. Procedural complexity and ownership opacity yield voting pathologies that undermine the integrity of the voting mechanism. However,blockchain offers a revolutionary solution. It enables the tracing of share ownership to former and current shareholders,and thus,promises to mitigate or eliminate voting pathologies. Notwithstanding,adoption remains largely contingent on resolving current regulatory gaps and technical design issues. © 2020 Universidad Pompeu Fabra. All Rights Reserved.
[Reforma de los sistemas de votación y retención de acciones en los Estados Unidos]
Keywords: Blockchain; Indirect holding system; Voting pathalogies; 59 Ciencia Política::5905 Vida política::5905.01 Elecciones; ODS 16 - Paz, justicia e instituciones sólidas